1994
DOI: 10.1007/bf00184113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium citrate and phytin on reducing urinary calcium excretion in rats

Abstract: The aim of this study was to determine and compare the effects of both magnesium citrate and phytin on reducing urinary calcium excretion under high-calcium-diet conditions during single and combined treatments. An animal experiment was carried out over a period of 4 weeks in 35 male rats. Urinary calcium excretion was reduced significantly by magnesium citrate and/or phytin in rats fed on high-calcium diets. The hypocalciuric effect of magnesium citrate was more evident than that of phytin. Urinary magnesium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Several animal studies have suggested hypomagnesiuria as a risk factor for stone formation [18][19][20][21]. In vivo, Mg inhibits stone formation in hyperoxaluric rats [22]. Some studies demonstrated that urinary Mg excretion is not significantly different in stone patients and healthy controls [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…Several animal studies have suggested hypomagnesiuria as a risk factor for stone formation [18][19][20][21]. In vivo, Mg inhibits stone formation in hyperoxaluric rats [22]. Some studies demonstrated that urinary Mg excretion is not significantly different in stone patients and healthy controls [23,24].…”
Section: Discussionmentioning
confidence: 98%